The effectiveness of The HR function in driving Talent Management Practices at an Electricity Company - Mtetwa, Trevor Ncamiso (Technium Social Sciences Journal, 2025)
Over the years HR departments have been accused of prioritising transactional functions over the strategic functions that drive business results. In addition, the changing nature of the business environment together with the pressure from business executives for HR to contribute value to business, HR departments find themselves compelled to demonstrate their efficiency and effectiveness in supporting the strategic imperatives of business. The aim of the study therefore was to investigate the effectiveness of the HR function in driving talent management at an electricity company. The study adopted a positivist descriptive approach. A sample of n=28 participants were selected from management employees using purposive sampling strategy. Data was collected via questionnaires and analysed with SPSS package. The researcher focused on management staff as they are responsible for implementing HR policies and work very closely with HR departments. The overall findings of the study indicated that the HR functions is not adequately managing talent management. Participants felt that there is no talent mind-set in the company and, there was great uncertainty about the link between the business strategy and talent strategy. Although respondents were content with development plans, they were not so satisfied with the implementation and meeting of development needs of employees. Other areas for improvement included employee retention and succession management.